Planes mínimos obligatorios en mercados de seguros de salud segmentados - Edmundo Beteta; Manuel Willington (Estudios de Economía, 2009)
– We analyze the effect of introducing a minimum mandatory health insurance plan in a segmented market in which high risks are affiliated to the public insurer and low risks to the private ones (market segmentation is endogenously obtained in our model). We assume both types of insurers must provide the basic plan, insurance is compulsory, and there is a minimum premium regulation. When we compare the equilibriums pre and post introduction of the basic health insurance plan, we find that an implicit subsidy mechanism operates that gives some solidarity to the system, even though no explicit risk compensation mechanism is introduced. For this implicit subsidy mechanism to operate, it is fundamental that not only the price of the basic plan is regulated but also the quality of the services included in such plan, and that the regulator is able to guarantee private insurers do offer the minimum plan to all risks.
Keywords: I11; I18; 330; health insurance; minimum basket of services; managed competition